The Efeect Of Giving Money, Goods, And Materials On The Electability Level Of Legeislative Candidates 2024 In Surabaya City - Salsabila Novia Jahroo; Siti Nur Rodiyah; Haniffah Widia Ananta; Anggraeny Puspaningtyas (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN-COMMUNITY OF RESEARCH LABORATORY, 2025)
This study aims to analyze the extent to which the provision of money, goods, and materials influences the electability of legislative candidates in the 2024 Election in Surabaya City. The research approach used is a quantitative approach with data collection through the distribution of questionnaires to 100 respondents domiciled in Wonokromo and Sukolilo Districts. The data obtained were analyzed using multiple linear regression methods with the help of SPSS software version 26. The results of the analysis show that the three independent variables, namely the provision of money (X₁), the provision of goods (X₂), and the provision of materials (X₃), have a positive and significant influence on the dependent variable, namely the electability of legislative candidates (Y). Among the three, the provision of goods variable has the strongest influence. These findings indicate that the practice of money politics in its various forms still plays an important role in shaping voter behavior in urban areas such as Surabaya City